2021
DOI: 10.1021/acs.accounts.1c00114
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Applications of Porphyrin Derivatives

Abstract: Conspectus Porphyrin derivatives are ubiquitous in nature and have important biological roles, such as in light harvesting, oxygen transport, and catalysis. Owing to their intrinsic π-conjugated structure, porphyrin derivatives exhibit characteristic photophysical and electrochemical properties. In biological systems, porphyrin derivatives are associated with various protein molecules through noncovalent interactions. For example, hemoglobin, which is responsible for oxygen transport in most vertebrates, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(76 citation statements)
references
References 69 publications
1
75
0
Order By: Relevance
“…However, SDT suffers from some inherent limitations, such as the poor tumor accumulation of small-molecule sonosensitizers and the lower quantum yield of inorganic sonosensitizers ( Liang et al, 2020 ). Nowadays, porphyrin and its derivatives are the most extensively used sonosensitizers in SDT due to their various unique properties ( Park J. M. et al, 2021 ). Nevertheless, the small-molecule porphyrins have low chemical and biological stability and are toxic to sensitive skin, which may lead to decreased therapeutic efficacy ( Ma et al, 2019 ).…”
Section: Serum Albumin-based Nanovehicle-assisted Cancer Theranosticsmentioning
confidence: 99%
“…However, SDT suffers from some inherent limitations, such as the poor tumor accumulation of small-molecule sonosensitizers and the lower quantum yield of inorganic sonosensitizers ( Liang et al, 2020 ). Nowadays, porphyrin and its derivatives are the most extensively used sonosensitizers in SDT due to their various unique properties ( Park J. M. et al, 2021 ). Nevertheless, the small-molecule porphyrins have low chemical and biological stability and are toxic to sensitive skin, which may lead to decreased therapeutic efficacy ( Ma et al, 2019 ).…”
Section: Serum Albumin-based Nanovehicle-assisted Cancer Theranosticsmentioning
confidence: 99%
“…ROS react with diffusion limited kinetics with a range of biochemical structures in cells such as lipids, aromatic amino acids, the heterocyclic bases, the backbone of nucleic acids, and flavonoids to induce oxidative damage to the cell, thereby causing cell death via apoptosis or necrosis [ 7 ]. Porphyrins are the most common and efficient photosensitizers used in PDT because of their absorption in the visible range of the electromagnetic spectrum, long-lived triplet excited state, and efficient phototoxicity toward cancer cells [ 8 ]. It is believed that these compounds selectively bind to and accumulate in tumor cells, thereby protecting normal tissue against a phototoxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we designed at wo-photon NIR-II-activated photooxygenation catalyst based on DSM-encapsulated HOF (denoted as DSM@n-HOF-6, DSM = 4-[p-(dimethylamino)styryl]-1-methylpyridinium). Meso-tetrakis(carboxyphenyl)porphyrin (TCPP), as aw idely used photosensitizer [73,74] and ac ommon linker for fabricating MOFs or COFs, [75,76] was chosen as the building blocks.P eriodic integration of TCPP into HOFs can not only effectively prevent the self-quenching effect and improve the accessibility of oxygen, [77][78][79] but also significantly enhance the solubility and biocompatibility.U nder 1040 nm NIR-II irradiation, the up-conversion fluorescence of DSM in n-HOF-6 could be absorbed by TCPP to generate singlet oxygen ( 1 O 2 ) for Ab oxygenation (Scheme 1). In vitro experiments demonstrated that Ab could be efficiently oxidized and aborted aggregation behavior.F urther,f or crossing the blood-brain barrier (BBB) and improving Ab selectivity,targeted peptide KLVFFAED (KD8) was conjugated to DSM@n-HOF-6 (denoted as DSM@n-HOF-6@KD8).…”
Section: Introductionmentioning
confidence: 99%